THERMAL CONDUCTIVITY VALUES OF SOME SANDSTONES AND SHALES FROM THE BELAIT FORMATION - Masnan, Safiq (Geological Society of Malaysia, 2010)
The Belait Formation has been found to mainly consist of alternating sandstone and shale with conglomerate as the basal unit. There are five main facies that could be classified in the Belait Formation. 1) Sandstone, 2) Sandstone with Clay Drapes, 3) Sandstone with Carbonaceous Material, 4) Shale, and 5) Conglomerate. Thermal conductivity analysis was done on the rock samples to understand the heat transfer between different rock facies. Apart from that, understanding the thermal conductivity characteristics enhances basin modeling and reservoir characterization. The general objective of this study was to estimate the thermal conductivities of rocks belonging to the Belait Formation and to link this information to the properties any possible signature trends that might bench mark the Formation. The study shows that there is an inverse relationship between the thermal conductivity and petrophysical properties such as porosity and particle size. The sedimentary rocks of the Belait Formation tend to have thermal conductivity values that are controlled by the internal fabric of the rocks. The relationship between thermal conductivity, porosity and particle size suggests that the trend line may be a unique signature for the Belait Formation.